PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN KONSUMEN MEMBELI PUPUK UREA NITREA PRODUKSI PUPUK INDONESIA DAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING - Muktar, Irvan Afandi; Pradiani, Theresia; Maskan, Moh. (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This research aims to analyze the effect of price and product quality on purchasing decisions and its impact on brand image as an intervening variable among consumers who buy Urea Nitrea fertilizer. The population in this study consists of consumers who have purchased Urea Nitrea fertilizer at the agricultural store CV. Tani Anda Mandiri, with a sample of 100 farmers. The sampling technique used is purposive sampling, and the data analysis method employed is path analysis with the Sobel test using the SPSS 29 data processing application. The research results show that price has a direct and significant influence on purchasing decisions, product quality has a direct and significant influence on purchasing decisions, price has a direct and significant influence on brand image, product quality has a direct and significant influence on brand image, brand image has a direct and significant influence on purchasing decisions, price has an indirect and significant influence on purchasing decisions through brand image, and product quality has an indirect and significant influence on purchasing decisions through brand image. Keywords: Price; Product Quality; Purchasing Decision; Brand Image